Protocol: validation of the INCODE barometer to measure the innovation compe-tence through the Rasch Measurement Theory - Lidia Sanchez; Beatriz Blanco; Juan A. Marín-García (WPOM : Working Papers on Operations Management)
This communication presents a protocol in order to show the different phases that must be followed in order to validate the INCODE barometer, which is used to measure the innovation competence, with Rasch Measurement Theory. Five phases are stated: dimensionality analysis, individual reliability and validity analysis of ítems and persons, global reliability and validity analysis, and cathegory analysis.